Regional Governance in der grenzüberschreitenden Zusammenarbeit. - Zäch, Christian; Pütz, Marco (Routledge, 2014)
Since 1990, cross-border cooperation in the European Union (EU) has been funded by the INTERREG programs. The planning and implementation of INTERREG projects, as well as the preparation of regional development strategies in each INTERREG program area, involves state and non-state actors. The different institutional frameworks of the EU and the participating nations makes cross-border cooperation a complex task of coordination. This article aims to clarify the role of INTERREG in the development of cross-border governance in the Lake Constance area. The main influence of INTERREG up until Funding Phase III (2000-2006) can be seen in the involvement of new actors from economics and civil society. In the subsequent funding phase (IV), which introduced strict and detailed guidelines for project application and implementation, thus complicating access to INTERREG funding, the involvement of new non-state actors in INTERREG projects seems to be declining. Today, the most important actor in cross-border cooperation is the International Lake Constance Conference (IBK), which is also supported by INTERREG funding. Although, IBK moderately institutionalized its structure in recent years, currently there are no cross-border institutions that would be able to solve severe cross-border conflicts, e.g. aircraft noise in southern Germany caused by the airport in Zurich. In addition, the large number of cross-border institutions sometimes leads to redundancies and inefficiencies in the governance of the Lake Constance area. However, since the region is not as peripheral as some other European regions, the dependence on public funds such as INTERREG is not as essential as may be the case elsewhere.
Regional Governance in Crossborder Collaborations - An Analysis of the "INTERREG IV Programm Alpenrhein-Bodensee-Hochrhein".
Keywords: Raumplanung; Region; Regionalpolitik; Kooperation; EU-Projekt; Projektbericht; Regional Governance; Fallstudie; Grenzüberschreitende Zusammenarbeit; Grenzüberschreitende Planung